The Effects of Artificial Lake Space on Satisfaction and Restorativeness of the Overall Environment and Soundscape in Urban Parks - Qi, Ying; Fang, Xingyue; Gao, Tian; Qiu, Ling (Frontiers in Built Environment, 2021)
Several studies have proven that soundscape in blue space is conducive to human health and well-being, but few studies have explored which blue space characteristics would contribute to a better soundscape and visiting experience. Therefore, an on-site questionnaire investigation was conducted at two artificial lakes in Xi’an, China. The eight Perceived Sensory Dimensions (PSDs) as a landscape assessment tool were applied to identify the characteristics of artificial lake space in urban parks. The results showed that (1) In artificial lake space, overall environment and soundscape reached a very satisfactory level in general, while the respondents’ perceived level of overall restorativeness and soundscape restorativeness as just medium, which indicated that the quality of artificial lake space needs to be improved. (2) According to people’s perceptions, artificial lake spaces had the most obvious characteristics of prospect, social and space; serene and nature were medium; refuge, rich in species, and culture were the least. (3) The eight PSDs of artificial lake space, except for social, were positively correlated with soundscape satisfaction, overall satisfaction, soundscape restorativeness, and overall restorativeness. Moreover, among them, serene was the most significant characteristic in artificial lake space. These findings could be instructive to the design of urban parks with artificial lakes for improving users’ visiting satisfaction and restorativeness.